Seasonal variation of agility, speed and endurance performance in young elite soccer players - Dragijsky, M.; Maly, T.; Zahalka, F.; Kunzmann, E.; Hank, M. (Sports, 2017)
The aim of this study was to investigate changes in the linear running speed (LRS) for 30 m, change of direction speed (CODS), and endurance in young elite Czech soccer players. The following tests were conducted to assess CODS and endurance: Agility 505 turning toward the dominant (A505DL) and non-dominant lower limb (A505NL); Illinois Agility Test (IAT); and intermittent test (Yo-Yo IRT1). During the soccer season, we investigated performance at the following time periods: the start (t1) and the end of the pre-season period (t2); during (t3) and at the end of the competitive period (t4). Repeated measurement analysis of variance revealed a significant effect of time period on selected fitness parameters (p < 0.05). Post hoc analysis for test A505DL revealed significant improvements of performance at t3 (2.71 ± 0.08 s) and t4 (2.72 ± 0.06 s) compared to t1 (2.81 ± 0.09 s). A505NL was significantly different between t1 (2.83 ± 0.09 s) and t2 (2.76 ± 0.09 s), t3 (2.7 ± 0.07 s) and t4 (2.71 ± 0.09 s). Performance of CODS at t1 for the IAT (18.82 ± 0.56 s) was significantly lower (p < 0.05) than any other time period (t2 = 18.52 ± 0.63 s, t3 = 17.94 ± 0.51 s, t4 = 17.89 ± 0.66 s). The power of LRS was significantly different at t3 (4.99 ± 0.15 s), and t4 (4.98 ± 0.17 s) compared to t1 (5.15 ± 0.21 s), and t2 (5.07 ± 0.14 s). For the Yo-Yo IRT1 test, we observed a significant increase in performance between t1 (625.26 ± 170.34 m), t2 (858.95 ± 210.55 m), and t3 (953.68 ± 229.88 m). These results show the impact of soccer season time period on young soccer player performance and may further serve as a basis for comparison with similar research conducted by peers. These results may aid sports practice for clinicians, conditioning coaches, soccer coaches and physiotherapeutic coaches.